2004
DOI: 10.1111/j.1464-410x.2004.05033.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper tract surveillance in primary bladder cancer follow‐up

Abstract: use surveillance in selected patients, i.e. those with carcinoma in situ (47%), multiple bladder tumours at first presentation (39%) and after cystectomy (70%), and 118 (39%) use upper tract surveillance on all patients with a history of bladder cancer. The median (range) screening interval was 24 (12-60) months and surveillance continued for a median of 10 (2 to indefinite) years, continuing for an indefinite period in 33%. CONCLUSIONSMost urologists use upper tract surveillance in patients with bladder cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…To date, there seems to be no established protocol to detect secondary UUTCs after TUR of superficial bladder cancer. In particular, the significance of routine IVU has been controversial [1,2,6–9,13], e.g. Wlazer and Soloway [8] reported that routine follow‐up IVU was neither cost‐effective nor necessary, considering the low incidence of UUT recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, there seems to be no established protocol to detect secondary UUTCs after TUR of superficial bladder cancer. In particular, the significance of routine IVU has been controversial [1,2,6–9,13], e.g. Wlazer and Soloway [8] reported that routine follow‐up IVU was neither cost‐effective nor necessary, considering the low incidence of UUT recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk of UUT recurrence after TUR for superficial bladder cancer is low, at 2-6% [1][2][3][4][5], most urologists use UUT surveillance in patients treated by TUR for superficial bladder cancer. However, there is wide variation in the categories used for patient selection, and in the duration and interval for which surveillance continues [6][7][8][9]. For example, based on responses to a questionnaire from 301 urologists in the BAUS, Enver et al [9] reported that 54% of urologists use surveillance in selected patients, while 39% use UUT surveillance in all patients with a history of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If there was no evidence of a tumour on cystoscopy, but the mucosa had an abnormal appearance or if cytology findings were positive, bladder biopsies were taken. If the biopsies were negative, the UUT was explored by CT and/or ureteroscopy [4]. We defined a recurrence either in situ in the bladder or in the UUT as local recurrence.…”
Section: Methodsmentioning
confidence: 99%
“…These studies were performed in patients submitted to radical cystectomy because of various types of bladder cancer. In addition, the lack of guidelines regarding patient selection and the interval and duration of surveillance results in wide variations in practice (10). There are no studies assessing the prognostic factors for metachronous UUT TCC after radical cystectomy for primary invasive bladder cancer by multivariate analysis.…”
Section: Introductionmentioning
confidence: 99%